Newly Identified Gross Human Anatomy: Eight Paired Vestigial Breast Mounds Run along the Embryological Mammary Ridges in Lean Adults. Issue 10 (October 2021) - Teplica, David; Kovich, Grant; Srock, Jamey; Whitaker, Robert; Jeffers, Eileen; Wagstaff, David A.
Abstract : Background: Although isolated accessory breasts have been reported in many locations on the torso, we noted that lean men presenting for liposuction had mounds of fullness in a curvilinear array (axilla to groin) consistent with the configuration of the embryological mammary ridge. We hypothesized that grid mapping and pinch testing would elucidate the pattern of fullness and its relation to the "milk line." Methods: Twenty lean participants (10 men, 10 women) each underwent standardized photography and grid mapping of anterior torsos. We then pinch-tested each for subcutaneous fullness in 250 standardized loci. We used plotted pinch values and OLS regression models to determine if focal fullness corresponded to published configurations of the embryologic mammary ridge. Results: We identified a pattern of paired mounds in all participants running bilaterally in curved linear arrays from axillae to groin in the exact form of milk lines. Regression models applied to the male and female pinch data indicated that focal thickness matched mammary ridge configurations in all subjects ( P = 0.023 for men, <0.001 for women). Fatty fullness never appeared elsewhere on the anterior torsos. Conclusions: The linear pattern of paired focal fat mounds present on the anterior torsos is consistent with the paths of embryological mammary ridges, suggesting these focal fat pads are of breast origin. The consistent mounds are distinct from general subcutaneous fullness and therefore represent a new finding of gross human anatomy. We recommend further research to define differential physiology of distinct subpopulations of yellow fat and clinical implications.